Laminated Monolithic Perovskite/Silicon Tandem Photovoltaics. Issue 27 (9th June 2022) - Roger, Julie; Schorn, Luisa K.; Heydarian, Minasadat; Farag, Ahmed; Feeney, Thomas; Baumann, Daniel; Hu, Hang; Laufer, Felix; Duan, Weiyuan; Ding, Kaining; Lambertz, Andreas; Fassl, Paul; et al.
Abstract: Perovskite/silicon tandem photovoltaics have attracted enormous attention in science and technology over recent years. In order to improve the performance and stability of the technology, new materials and processes need to be investigated. However, the established sequential layer deposition methods severely limit the choice of materials and accessible device architectures. In response, a novel lamination process that increases the degree of freedom in processing the top perovskite solar cell (PSC) is proposed. The very first prototypes of laminated monolithic perovskite/silicon tandem solar cells with stable power output efficiencies of up to 20.0% are presented. Moreover, laminated single‐junction PSCs are on par with standard sequential layer deposition processed devices in the same architecture. The numerous advantages of the lamination process are highlighted, in particular the opportunities to engineer the perovskite morphology, which leads to a reduction of non‐radiative recombination losses and and an enhancement in open‐circuit voltage ( V oc ). Laminated PSCs exhibit improved stability by retaining their initial efficiency after 1‐year aging and show good thermal stability under prolonged illumination at 80 ° C. This lamination approach enables the research of new architectures for perovskite‐based photovoltaics and paves a new route for processing monolithic tandem solar cells even with a scalable lamination process. Abstract : This work proposes an innovative fabrication method for perovskite‐based tandem photovoltaics. The lamination process recrystallizes the perovskite thin film and thereby unites two independent device half‐stacks at elevated temperatures and pressures. Notably, the first prototypes of laminated monolithic perovskite/silicon already demonstrate stable power conversion efficiencies up to 20%.